Textual Exposures Photography in Twentieth Century Spanish American Narrative Fiction - Russek, Dan (Latin American & Caribbean Studies, 2015)
This book examines how twentieth-century Spanish American literature has registered photography's powers and limitations, and the creative ways in which writers of this region of the Americas have elaborated in fictional form the conventions and assumptions of this medium. While the book is essentially a study of literary criticism, it also aims to show how texts critically reflect upon the media environment in which they were created. The writings analyzed enter a dialogic relation with visual technologies such as the x-ray, cinema, illustrated journalism, and television. The study examines how these technologies, historically and aesthetically linked to the photographic medium, inform the works of some of the most important writers in Latin America. Methodologically, the close readings of the texts centre on the figure of ekphrasis (defined as the verbal representation of a visual representation). The book is concerned with the thematic, symbolic, structural and cultural imprints photography leaves in narrative texts. The author relies on an immanent approach, reading the selected texts according to their own specificities and making the relevant thematic and structural connections between them drawing from a variety of sources in the fields of literary criticism and theory and history of photography.